Analysis Of The Application Of Fiqih Rules In DSN MUI Fatwa On Murabahah Agreement No. 04/DSN-MUI/IV/2000 - Ahmad Parlindungan Pasaribu; Ahsanul Rizki; Mawaddah Warohmah (Sean Institute, 2025)
The Law of Fiqh ( rules) fiqh ) in etymological is the basics or related principles​ with problems or types fiqh . Research This done For know implementation rules jurisprudence in transactions according to the DSN fatwa . Research This based on the results observations that discuss about review general about rules jurisprudence Good from aspect understanding , basics law , and its types , application rules jurisprudence in DSN-MUI Fatwa No. 4/DSN-MUI/IV/2000 . The research method used by the author use is method study library research where we search​​ from various source reference like books , journals , and e-book. Research results application of fiqh fatwa in transactions according to the DSN fatwa.